THE ROLE OF ELECTROTHERAPY AND PHYSICAL THERAPY IN THE RECOVERY OF CERVICAL ARTHROSIS - Ochiana Gabriela; Ochiana Nicolae (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
The purpose of this study concerning the role of electrotherapy and of physical therapy in the recovery of cervical arthrosis is to maintain a high quality family, social and professional activity, by eliminating the pain and the muscle contractures. The hypothesis that was the starting point of this paper was that: if we associate electrotherapy techniques and cervical spine alignment techniques to the recovery programme, the pain and the paresthesias will diminish until they fade away for good. The study was conducted on a number of 24 subjects with the diagnosis of cervical arthrosis, over a period of 6 months. The subjects in the experimental group were 12 and they benefited from electrotherapy and physical therapy, while those in the control group had only medication. The methods, procedures and the techniques used in the recovery for the subjects included in the experimental group were: TENS currents, ultrasounds, tractions on an axis, facilitation techniques and the adjustment of the cervical spine. The results materialized in: the disappearance of pain, of paresthesias and of muscle contractions obtain in a relatively short period of time, allows us to notice the benefit of associating electrotherapy and physical therapy to the recovery of cervical arthroses. The conclusions underline the importance of the position adopted during all the activities that require head flexion in order to prevent the rectitude of the cervical spine and implicitly the pain, the paresthesias and the contractures.